2012
DOI: 10.1080/15567036.2012.692756
|View full text |Cite
|
Sign up to set email alerts
|

Coal Permeability Damage Caused by Production Pressure Difference

Abstract: Due to the special physical and mechanical properties and gas production mechanism of coal reservoirs, the changes of their physical properties are different from those of conventional reservoirs during the coalbed methane development process, of which the dynamic change in permeability is the most significant. During the development process of coalbed methane, production pressure difference can promote gas desorption, but meanwhile, it brings serious damage on coal permeability. This study simulated this dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…EDR values that are too high indicate a fast drop in bottom hole pressure where too much gas is desorbed, causing gas locking in the reservoir which would result in far less than optimal outgassing. Furthermore, the effective stress on the coal reservoir will increase, decreasing permeability and gas production (Tao et al, 2012a). The relationship between the EDR and CBM well productivity is demonstrated in Fig.…”
Section: Equivalent Drainage Radius (Edr)mentioning
confidence: 98%
See 3 more Smart Citations
“…EDR values that are too high indicate a fast drop in bottom hole pressure where too much gas is desorbed, causing gas locking in the reservoir which would result in far less than optimal outgassing. Furthermore, the effective stress on the coal reservoir will increase, decreasing permeability and gas production (Tao et al, 2012a). The relationship between the EDR and CBM well productivity is demonstrated in Fig.…”
Section: Equivalent Drainage Radius (Edr)mentioning
confidence: 98%
“…A pressure drop rate that is too high can lead to a serious stress sensitivity in the coal reservoir, leading to a decline in permeability (Tao et al, 2012a;. A fast pressure drop will mobilize coal dust in the reservoir, blocking the gas seepage channels and reducing gas production.…”
Section: Decline Rate Of Working Fluid Level During the Initial Produmentioning
confidence: 98%
See 2 more Smart Citations
“…Then the stronger methane power field made gas evolution under the same declining pressure more easily [30,31]. It was also found that a higher critical reservoir ratio shortened the time of CBM well drainage, which reduced the damage caused by effective stress on the permeability of reservoir during the drainage and depressurization stage, weakened the negative effect of fracturing fluid on critical desorption pressure of reservoir, and increased the aerodynamic force [3,32]. The critical reservoir ratio is considered to be a profit-type index for reservoir evaluation; (6) Permeability.…”
Section: Index System Constructionmentioning
confidence: 99%